Group music therapy with adolescent asylum seekers at a temporary reception center : a phenomenological study - Mbeutcha, Alexis (2020)
The purpose of this phenomenological study was to; (1) explore the experience of teenage asylum-seekers as they went through 20 sessions of group music therapy while waiting for the resolution of the asylum claims at the temporary reception center for refugees and (2) discover the type of challenges that a therapist can face when working with teenagers in a situation of crisis and what can be the possible steps taken in order to overcome those challenges. By adopting a phenomenological approach, the goal was that in exploring the essence of the participants’ experience, the findings would show a clearer understanding of how music therapists, social workers or anyone working in connection with adolescent asylum-seekers could contribute in improving the condition of children refugees in situations of crisis. The research questions that guided this inquiry where the as follows: what is the nature of the experience of adolescence asylum-seekers as they go to group music therapy in a reception center? And what kind of challenges can therapists expect to face when working under those conditions? The research findings showed that our teenage participants experienced (1) a sense of joy and improved mood, (2) a connection to their country in moments of nostalgia, (3) increased confidence and overcoming sense of shyness, (4) a sense of developing personal identity through music, (5) a sense of awareness into how music can affect them, and gratitude for that they saw an opportunity to take part in group music therapy. The study also uncovered that enormous challenges can arise for any therapist working with adolescents of foreign background mostly due to cultural and linguistic differences, post-migration related issues, and equally the need to preserve anonymity in the case of an ongoing asylum. It was also found that while those challenges can be overcome by the therapist adopting the right approach and right attitude, the level of challenge can be almost overwhelming, making such projects difficult to undertake without sufficient support.